PHARMACOTHERAPY ANALYSIS OF ACUTE ST-ELEVATION MYOCARDIAL INFARCTION IN HOSPITALS OF VARIOUS TYPES - R. M. Magdeev; O. V. Reshetko; E. Y. Rudnichenko; N. V. Furman; P. V. Dolotovskaya; T. Y. Grozdova; L. N. Volkova (Столичная издательская компания, 2016)
Aim. To evaluate pharmacotherapy of ST-elevation myocardial infarction (STEMI) in cardiology departments of Saratov hospitals of various types. Material and methods. The retrospective pharmacoepidemiological study was carried out with involved of 424 hospital charts of STEMI patients, discharged during the year from the cardiology department of Saratov municipal hospital (MH; n=216) and emergency cardiology department of Saratov clinical hospital (CH; n=208). Results. The real practice in the audited hospitals are not fully consistent with current guidelines for the STEMI patients management. The relationship between guidelines compliance and hospital type is clearly seen. Doctors in MH in comparison with them in CH more often prescribed respiratory analeptics (13.4% vs 5.3% , respectively), metabolic drugs (63.4% vs 37.5%, respectively) and rarer used beta-blockers (50% vs 88.9%, respectively) and thrombolytic therapy (3.7% vs 51%, respectively). In MH dipyridamole was used in 9.6% of patients as an alternative to the acetylsalicylic acid, and clopidogrel was not prescribed. At the same hospital clotting time was determined for monitoring of heparin therapy. Statins were rare used in both hospitals (26% in MH vs 40% in CH). Conclusion. The real clinical practice of STEMI patients management in Saratov hospitals are not completely consistent with current clinical guidelines. There are differences in STEMI patients therapy depending on hospital type.